Retrieval-Extinction and Relapse Prevention: Rewriting Maladaptive Drug Memories? - Kuijer, Eloise J.; Ferragud, Antonio; Milton, Amy L. (Frontiers in Behavioral Neuroscience, 2020)
Addicted individuals are highly susceptible to relapse when exposed to drug-associated conditioned stimuli (CSs; “drug cues”) even after extensive periods of abstinence. Until recently, these maladaptive emotional drug memories were believed to be permanent and resistant to change. The rediscovery of the phenomenon of memory reconsolidation—by which retrieval of the memory can, under certain conditions, destabilize the previously stable memory before it restabilizes in its new, updated form—has led to the hypothesis that it may be possible to disrupt the strong maladaptive drug-memories that trigger a relapse. Furthermore, recent work has suggested that extinction training “within the reconsolidation window” may lead to a long-term reduction in relapse without the requirement for pharmacological amnestic agents. However, this so-called “retrieval-extinction” effect has been inconsistently observed in the literature, leading some to speculate that rather than reflecting memory updating, it may be the product of facilitation of extinction. In this mini review article, we will focus on factors that might be responsible for the retrieval-extinction effects on preventing drug-seeking relapse and how inter-individual differences may influence this therapeutically promising effect. A better understanding of the psychological and neurobiological mechanisms underpinning the “retrieval-extinction” paradigm, and individual differences in boundary conditions, should provide insights with the potential to optimize the translation of “retrieval-extinction” to clinical populations.